Navigating Green Banking Disclosure: How Slack Resources Moderate Governance Effects - Muhammad Gias; Suripto Suripto; Mediya Destalia (Eastasouth Institute, 2026)
This study aims to analyze the influence of corporate governance, financial slack, human resource slack, return on assets, and non-performing loan on green banking disclosure among banking companies listed on the Indonesia Stock Exchange during the 2022–2024 period. This research is based on Stakeholder Theory. The study uses secondary data derived from annual and sustainability reports of 16 banking companies and applies panel data regression. Data collection technique used in this research is documentation study. The findings reveal that corporate governance has a significant positive effect on green banking disclosure, while return on assets and non-performing loan demonstrate significant negative effects. Conversely, financial slack and human resource slack show no significant partial influence. The simultaneous test indicates that all independent variables collectively have a significant effect on green banking disclosure, suggesting that sustainability disclosure is shaped by a combination of governance quality, resource availability, profitability, and credit risk management. Moderation testing further shows that neither financial slack nor human resource slack moderates the relationship between corporate governance and green banking disclosure.